Moist Static Energy Transport Trends in Four Global Reanalyses: Are They Downgradient?. Issue 20 (17th October 2022) - Clark, Joseph P.; Feldstein, Steven B.; Lee, Sukyoung
Abstract: Trends in moist static energy (MSE) transport are investigated for the years 1980 through 2018 using four different reanalysis data sets. The reanalysis data sets show agreement in the eddy MSE transport trends and the latitudinal structure of the MSE trends, but vary widely in the trend of the flux of the climatological zonal mean MSE by the anomalous zonal mean meridional wind. The latter dominates the total MSE transport trends in all four data sets. Therefore, none of the four total MSE flux trends is downgradient of the corresponding MSE trend. Further analysis of the MSE trends reveals that dry static energy increases strongly dominate MSE trends at all latitudes, including in the tropics where climate models and theory predict latent energy increases to dominate. As changes in MSE transport are routinely assumed to be downgradient when interpreting changes in climate, including Arctic amplification, further investigation of reanalysis MSE transport is warranted. Plain Language Summary: The Earth receives more energy than it loses over lower latitudes and loses more energy than it receives over high latitudes. Consistently, the atmospheric circulation fluxes much of the excess energy from low latitudes toward high latitudes where there is an energy deficit. This poleward movement of energy in the atmosphere plays a crucial role in shaping the climate, but it remains unclear how this energy transport will change as the climate warms. In this study, we investigate how energy transport has changed in recent decades using four different reanalysis data sets, data sets that obtain global coverage by combining atmospheric measurements with numerical models. We find that data sets do not agree on the trends in the energy transports which limits the extent to which they can be used to investigate energy transports. Nonetheless, reanalysis data sets do agree on certain aspects that contrast notably with climate models. First, energy transport trends in the reanalysis data sets do not flux energy from locations with high energy to locations with low energy. Second, reanalysis temperature increases drive greater increases in energy than that from water vapor, whereas in climate models water vapor increase is the most important contributor to the energy over the tropics. Key Points: Reanalysis data sets disagree on interannual variability and trends in moist static energy (MSE) transport Reanalysis MSE transport trends do not show a clear flux‐gradient response to the MSE gradient trend Reanalysis MSE transport trends are dominated by fluxes of time‐mean dry static energy by anomalous zonal mean meridional winds